An enhancement of Smart Traffic Light in LoRa network for small scale area / Lutfi Hadi Azizul Adry and Rafiza Ruslan - Azizul Adry, Lutfi Hadi; Ruslan, Rafiza (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Vehicles such as cars, motorcycles, trucks, busses etc. are increasing day by day due to convenient purposes. This phenomenon leads to traffic jam that can affect ones delay activities. A smart traffic light is needed to improve the traffic congestion. Implementing LoRa technology is one of the efficient way because of the long-distance coverage and low power consumption. This research built a prototype of three traffic lights using Cytron LoRa- RFM Shield and Passive InfraRed (PIR) Mini motion sensor. The prototype traffic lights work fine in three-way junction that can control the flow of the traffic. The result of functionality test and usability test shows that the traffic light is in good condition and accepted by 93.5% of the respondents. In addition, the prototype is agreed 100% by the respondent for improving the traffic flow safety. For the future work, artificial intelligence (AI) features can be implemented to replicate the real time traffic light for a more efficient system.